Transforming Waste into Value: Developing Shrimp Powder Broth in Sungsang Village - Hamira; Sari, Dwi Darma Puspita; Nida, Rahma; Aini, Halia Butra; Nabawi, Denny (Universitas Djuanda Bogor, 2025)
The Sungsang area in Banyuasin Regency, South Sumatra, has a nutrient-rich estuary ecosystem that supports aquatic biota such as fish, shrimp, and crabs. Residents mostly work as fishermen and process fishery products into value-added products, such as shrimp paste and crackers. However, shrimp shell waste is often neglected despite its high economic potential. Community service activities in Sungsang IV Village aim to increase environmental awareness and encourage innovation in the utilization of shrimp shell waste. The method of this community service activity is through socialization and training in producing powdered broth from shrimp shell waste. Through training, the community was given an understanding of sustainable waste management and the skills to process shrimp shell waste into economical powdered broth. As many as 80% of participants stated that they understood the material very well, and the program succeeded in reducing environmental pollution while increasing local income. With high enthusiasm, the program is relevant to the community's needs, providing positive economic, social, and ecological impacts.